Preparation and evaluation of Brucella T4SS recombinant proteins in serodiagnosis of human brucellosis based on TMT-based proteomics technology - Qi Wu; Chen Sun; Liping Guo; Yujia Xie; Jinpeng Zhang; Jinpeng Zhang; Dehui Yin; Dehui Yin (Frontiers in Cellular and Infection Microbiology)
IntroductionBrucellosis, a significant zoonotic infectious disease, poses a global health threat. Accurate and efficient diagnosis is crucial for prevention, control, and treatment of brucellosis. VirB proteins, components of the Type IV secretion system (T4SS) in Brucella, play a pivotal role in bacterial virulence and pathogenesis but have been understudied for their diagnostic potential.MethodsTandem Mass Tag (TMT) proteomics technology was utilized to identify highly expressed VirB proteins from wild-type Brucella strains. Recombinant T4SS proteins were prepared, and an indirect ELISA method was established for serological diagnosis of human brucellosis.ResultsSeven T4SS proteins (rVirB3, rVirB4, rVirB9, rBMEII0036, rVirB8, rVirB11, and rVirB10) were expressed used to construct the indirect ELISA method which showed high diagnostic accuracy. Sensitivity and specificity of the proteins exceeded 0.9100 and 0.9167, respectively, demonstrating good performance comparable to traditional LPS and Rose Bengal Ag antigens. Cross-reactivity was observed in a limited number of serum samples from febrile patients without brucellosis.ConclusionsThe study highlights the potential of VirB proteins as novel diagnostic antigens for human brucellosis. Future research can further optimize the use of VirB proteins in diagnostic assays and explore their applications in vaccine development.